Enhanced blood–brain barrier penetration and glioma therapy mediated by a new peptide modified gene delivery system. (January 2015) - Yao, Hui; Wang, Kaiyuan; Wang, Yi; Wang, Shanshan; Li, Jianfeng; Lou, Jinning; Ye, Liya; Yan, Xueying; Lu, Weiyue; Huang, Rongqin
Abstract: Successful glioma gene therapy lays on two important factors, the therapeutic genes and efficient delivery vehicles to cross the blood–brain barrier (BBB) and reach gliomas. In this work, a new gene vector was constructed based on dendrigraft poly-l -lysines (DGL) and polyethyleneglycol (PEG), conjugated with a cell-penetrating peptide, the nucleolar translocation signal (NoLS) sequence of the LIM Kinase 2 (LIMK2) protein (LIMK2 NoLS peptide, LNP), yielding DGL-PEG-LNP. Plasmid DNA encoding inhibitor of growth 4 (ING4) was applied as the therapeutic gene. DGL-PEG-LNP/DNA nanoparticles (NPs) were monodispersed, with a mean diameter of 90.6 ± 8.9 nm. The conjugation of LNP significantly enhanced the BBB-crossing efficiency, cellular uptake and gene expression within tumor cells. Mechanism studies suggested the involvement of energy, caveolae-mediated endocytosis and macropinocytosis in cellular uptake of LNP-modified NPs. MTT results showed that no apparent cytotoxicity was observed when cells were treated with synthesized vectors. Furthermore, LNP-modified NPs mediated strongest and most intensive apoptosis on the tumor site, and the longest median survival time of glioma-bearing mice. All the results demonstrated that LNP is a kind of efficient CPPs especially for BBB-crossing application, and DGL-PEG-LNP/DNA is a potential non-viral platform for glioma gene therapy via intravenous administration.